THE SCIENTIFIC-PRACTICAL CONFERENCE THE PAIN. PROBLEMS AND SOLUTIONS 20 OCTOBER, 2015 - V. H. Timerbaev (Неотложная медицинская помощь)
The Scientific-Practical Conference The pain. Problems and Solutions 20 October, 2015.